PENERAPAN APLIKASI AKUNTANSI LAMIKRO BERDASARKAN SAK EMKM PADA USAHA MIKRO KECIL MENENGAH (STUDI KASUS PADA GILAPOLOS) - Achmad Wisnu Abdulloh Suratno; Dewi Saptantinah Puji Astuti; Fadjar Harimurti (Universitas Slamet Riyadi, 2020)
This study aims to (1) determine whether the LAMIKRO applicationprogram based on SAK EMKM is appropriate for Gilapolos. (2) To know thesteps of the LAMIKRO Application program at Gilapolos. This study usesqualitative and quantitative data by observing the development of Gilapolos,production and sales as well as data collection in the form of Gilapolos financialtransaction records. Data were collected by means of observation, interviews anddocumentation. The results show that (1) the LAMIKRO application based onSAK EMKM can be applied correctly to Gilapolos' business, (2) describes thesteps in operating the LAMIKRO application, from creating a LAMIKRO accountto getting results in the form of an income statement and a statement of financialposition.